BIDAYUH JAGOI (BIJAGOI) COMMUNITY'S DEPENDENCY ON NON-TIMBER FOREST PRODUCTS (NTFPS) IN BAU DISTRICT, SARAWAK, MALAYSIA - Tonga, Noweg; Alfred, Keleman; Julia, Nelson (Forestry Department Peninsular Malaysia, 2024)
Non-timber forest products (NTFPs) are important components of ecosystem services offered by forests. They offer a competitive advantage and directly benefit communities living in the vicinity of forest. The study was conducted in Bau District, Sarawak. It assessed the utilization and reliance of the BiJagoi community on NTFPs. Preliminary investigation and consultation were conducted with the community leaders, followed by group discussions and individual household interviews. The results showed that the BiJagoi community relies on NTFPs as secondary sources of medicine, firewood, food, and crafting materials. These NTFPs are primarily utilized for personal consumption. The community collects NTFPs mainly from outside the Jagoi Heritage Forest (JHF) and gathers them only when needed. The findings indicate that the BiJagoi community continues to rely on NTFPs for daily sustenance, with the utilization of firewood resources influenced by age. This study is important to help identify threats to JHF, support its conservation efforts, and serve as a baseline for achieving International Union for Conservation of Nature (IUCN) Greenlist Standard recognition.